Endure : mind, body, and the curiously elastic limits of human performance - Hutchinson, Alex (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2018)
"If you want to gain insight into the mind of great athletes, adventurers, and peak performers then prepare to be enthralled byAlex Hutchinson'sEndure."--Bear Grylls From the National Magazine Award-winning Runner's World columnist, frequent New Yorker online contributor, and Cambridge-trained physicist: a fascinating and definitive exploration of the revolutionary new science ofendurance and the secrets ofhuman performance. Alex Hutchinson, Ph.D.,revealswhy our individual limits may be determined as much by our head and heart, as by our muscles"--
"From the National Magazine Award-winning Runner's World columnist, frequent NewYorker.com contributor, and Cambridge-trained physicist: a fascinating and definitive exploration of the science of endurance and peak performance"--
Includes bibliographical references (pages 271-295) and index.
Keywords: Sports -- Physiological aspects; HEALTH & FITNESS / Exercise; SPORTS & RECREATION / Running & Jogging; SPORTS & RECREATION / Running & Jogging